Leprosy: epidemiology, pathology, immunology, prevention of disability and stigma - Lockwood, Diana N.J. (Henry Stewart Talks, 2022)
Epidemiology of leprosy, Transmission global figures, Leprosy and HIV, M. leprae genome -Immune response in tuberculoid and lepromatous patients, BCG vaccine and protection against leprosy, Disability in leprosy, Self-care and mental health in leprosy, Footwear, Covid and leprosy services, New Face for leprosy